PENGEMBANGAN REAKTOR SAMPAH UNTUK PENYELESAIAN MASALAH DI DAERAH URBAN: STUDI KASUS DI KOTA BANDUNG - Dzakiy, Uruqul Nadhif; Pringgabayu, Dematria; Hidayat, Agus Maolana; Fadh Hottob, Ahmad Sulthon; Purwandari, Icha Sofia; Azizah, Zaskia Nur; Akbar, Subhan Syariifi (Jurnal Pengabdian Kepada Masyarakat, 2024)
Waste reactors can help overcome waste problems in cities, including the city of Bandung. The hydrothermal reactor is one of various types of reactors that we design to convert organic waste into useful products that have a selling value comparable to fertilizer and animal feed. The people of Cangkuang Kulon sub-district, Bandung Regency, which is directly adjacent to the Cibaduyut shoe center area, Bandung City, will test the manufacture and use of this reactor. We hope that this community service effort can solve the waste problem in cities, especially in the city of Bandung.